Swept under the carpet: a qualitative study of patient perspectives on Long COVID, treatments, services, and mental health - Lisa D. Hawke; Anh T. P. Nguyen; Natasha Yasmin Sheikhan; Gillian Strudwick; Susan L. Rossell; Sophie Soklaridis; Stefan Kloiber; Roslyn Shields; Chantal F. Ski; David R. Thompson; David Castle (BMC Health Services Research, 2023)
Abstract Background A constellation of often disabling long-term physical symptoms enduring after an acute SARS-COV-2 infection is commonly referred to as Long COVID. Since Long COVID is a new clinical entity, research is required to clarify treatment needs and experiences of individuals affected. This qualitative descriptive study aimed to provide insight into Long COVID treatment and service experiences and preferences of individuals experiencing Long COVID and the intersections with mental health. Methods The study was conducted out of a tertiary care mental health hospital, with online recruitment from the community across Canada. A total of 47 individuals (average age = 44.9) participated in one of 11 focus groups between June and December 2022. Five focus groups were conducted with participants who had pre-existing mental health concerns prior to contracting SARS-CoV-2, and six were with people with Long COVID but without pre-existing mental health concerns. A semi-structured interview guide asked about service experiences and service preferences, including mental health and well-being services. Discussions were recorded, transcribed, and analyzed using codebook thematic analysis. Results When accessing services for Long COVID, patients experienced: (1) systemic barriers to accessing care, and (2) challenges navigating the unknowns of Long COVID, leading to (3) negative impacts on patient emotional well-being and recovery. Participants called for improvements in Long COVID care, with a focus on: (1) developing Long COVID-specific knowledge and services, (2) enhancing support for financial well-being, daily living, and building a Long COVID community, and (3) improving awareness and the public representation of Long COVID. Conclusions Substantial treatment barriers generate considerable burden for individuals living with Long COVID. There is a pressing need to improve treatment, social supports, and the social representation of Long COVID to create integrated, accessible, responsive, and ongoing support systems.